Psychological Characteristics of the Body Image of Middle-Aged Women in Organization of Interpersonal Interaction - Duisenbayeva , Ainur; Kariyev , Adlet; Baimoldina , Laura; Issayeva , Zhazira (Insight: the psychological dimensions of society, 2024)
The aim of the research is to identify psychological characteristics of the body image of middle-aged women in organization of interpersonal interaction. Methods. The research involved middle-aged women of 30–43 years (n = 221). The descriptive frequency characteristics of the sample: M = 36.72; SD = ±6.71; Me = 37.00; Mo = 35.00. Valid and reliable questionnaires were used: “The Multidimensional Body-Self Relations Questionnaire” (MBSRQ) (Cash, 2017); “The Body Image Questionnaire” (BIQ) (Skugarevskiy & Sivukha, 2006), “The Body Assessment” (BA) (Harris, 1969). “Fundamental Interpersonal Relationships Orientation–Behavior” (FIRO–B) (Schutz, 1959), “Diagnostics of Interpersonal Relationships” (DIR) (Leary, 1956). Retrospective analysis and generalization of scientific data on the research subject were used. The collected theoretical information and empirical data were substantiated, explained and systematized. Results. It was found that the parameter “average value of satisfaction with body parts” (AVSBP) with the largest number of significant correlations (three) – with authoritarianism (AT), egoism (EG) and aggressiveness (AG) – is the most dependent parameter of the body image in the octant dimensions of the psychogram. The authoritarian type is the most dependent type of interpersonal interaction. It was established that the parameter “average value of satisfaction with body parts” (AVSBP) with the largest number of significant correlations (two) – with inclusion (Iw) and control (Ce) – is the most dependent parameter of the body image in the dimensions of the parameters of interpersonal interaction. Control (Ce) with three inverse significant correlations – with “health status assessment” (HSA), “average value of satisfaction with body parts” (AVSBP) and “average value of concern about overweight” (AVCO) – is the most dependent parameter of interpersonal interaction. Discussion and conclusions. Middle-aged women assess their health status quite highly and demonstrate concern about their appearance. This category of women seldom tries to disguise their weight, mainly having moderate and, to a lesser extent, low satisfaction with their body parts. The vast majority of middle-aged female respondents have an inadequate perception of their body which is a strong argument for dissatisfaction with their body. The hypothesis is confirmed, i.e. the correlation between middle-aged women’s satisfaction with their body and certain indicators of interpersonal interaction was established. The obtained results can be used for conducting more large-scale research on identifying factors of interpersonal interaction in other areas of psychology.
Keywords: body assessment; body image; body mass index (BMI); inclusion; control; affection; personal body image